Digital Mind Mapping in Learning Journals (DMMILJ): A Pedagogical Innovation to Foster Self-Regulated Learning in Higher Education - Suriyah Satar; Nurbaya Nurbaya; Hanida Listiani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to develop and test the effectiveness of the Digital Mind Mapping in Learning Journal (DMMILJ) learning technique to improve students' Self-Regulated Learning (SRL) abilities in the Plant Development Structure course. This technique integrates digital concept mapping using applications such as Canva and Mind Meister with individual and group reflective journal practices. The development was carried out using the ADDIE model, which includes the stages of needs analysis, format design, product development, implementation in the experimental class, and effectiveness evaluation. The trial was conducted in one class of Biology Education students at Cenderawasih University using a one-group pretest-posttest design. The research instruments included a learning outcome test and an SRL questionnaire validated by experts. The validation results showed that the DMMILJ learning technique was highly valid with an average score above 92%. Data analysis using N-Gain showed an increase in learning outcomes of 67.86% (medium-high category). In addition, there was an increase in SRL scores from 70% to 75% (good category). These findings indicate that the DMMILJ technique encourages active engagement, strengthens reflective skills, and enhances students' ability to independently manage their learning strategies and goals. This technique can be recommended as an innovative digital-based learning strategy in higher education contexts. By merging visual mapping and narrative reflection in a digital ecosystem, this study offers a scalable and innovative learning strategy that aligns with the demands of 21st-century education. The DMMILJ technique significantly contributes to improving learning quality in schools and universities by fostering digital competence, deeper cognitive engagement, and self-directed learning, making it a valuable model for transforming science education in digital classrooms.